2020
DOI: 10.1177/2047487320916591
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical progression of systemic sclerosis-related cardiomyopathy

Abstract: Aims Cardiac involvement in patients with systemic sclerosis (SSc) is frequent and represents a negative prognostic factor. Recent studies have described subclinical heart involvement of both the right ventricle (RV) and left ventricle (LV) via speckle-tracking-derived global longitudinal strain (GLS). It is currently unknown if SSc-related cardiomyopathy progresses through time. Our aim was to assess the progression of subclinical cardiac involvement in patients with SSc via speckle-tracking-derived GLS. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…In this issue of the Journal, Stronati et al investigate the progression of subclinical biventricular cardiac involvement in patients with SSc using speckletracking-derived GLS. 12 At follow-up, conventional echocardiographic parameters did not differ from baseline, but both LV GLS and right ventricle (RV) GLS deteriorated significantly in the absence of overt fibrosis in cardiac magnetic resonance. Moreover, among patients who have experienced major clinical events during follow-up, the data showed a faster progression of RV GLS impairment.…”
Section: Subclinical Progression Of Systemic Sclerosis (Ssc)-related mentioning
confidence: 89%
“…In this issue of the Journal, Stronati et al investigate the progression of subclinical biventricular cardiac involvement in patients with SSc using speckletracking-derived GLS. 12 At follow-up, conventional echocardiographic parameters did not differ from baseline, but both LV GLS and right ventricle (RV) GLS deteriorated significantly in the absence of overt fibrosis in cardiac magnetic resonance. Moreover, among patients who have experienced major clinical events during follow-up, the data showed a faster progression of RV GLS impairment.…”
Section: Subclinical Progression Of Systemic Sclerosis (Ssc)-related mentioning
confidence: 89%
“…Systemic sclerosis patients also show differences in strain imaging via echocardiography as compared to controls. Studies have shown both regional and global LV longitudinal systolic strain (LVLSS) is significantly lower in SSc patients than controls and is most pronounced in the endocardial layer of the LV ( 56 , 57 ). Furthermore, SSc patients with lower global LVLSS were more likely to have elevated C-reactive protein values suggesting greater inflammation.…”
Section: Left Ventricular Dysfunctionmentioning
confidence: 99%
“…Also, acute myocardial infarction (AMI) in patients with SSc was shown to be associated with higher risk of recurrent adverse cardiovascular events and death, but not bleeding in comparison to other patients with AMI 9 . Of note, patients with SSc and adverse cardiovascular events had much worse prognosis than patients with other systemic connective tissue diseases, such as rheumatoid arthritis or systemic lupus erythematosus 10 The cardiac involvement in SSc is thought to be related to microvascular dysfunction and resultant subclinical systolic dysfunction reflected by impaired left ventricular (LV) global longitudinal strain, which even precede development of pulmonary hypertension 11 . Patients with cardiovascular incidents were characterized by cardiac magnetic resonance alterations, such as early and late gadolinium enhancement 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac involvement in SSc is thought to be related to microvascular dysfunction and resultant subclinical systolic dysfunction reflected by impaired left ventricular (LV) global longitudinal strain, which even precede development of pulmonary hypertension 11 . Patients with cardiovascular incidents were characterized by cardiac magnetic resonance alterations, such as early and late gadolinium enhancement 12 .…”
mentioning
confidence: 99%